People's Republic of China-Hong Kong Special Administrative Region : Financial Sector Assessment Program-Detailed Assessment of Observance-HKFE Clearing Corporation Limited (HKCC) Principles for Financial Market Infrastructures. (IMF Staff Country Reports; Country Report ;, 2021)
The HKFE Clearing Corporation Limited (HKCC) observes the CPSS/IOSCO Principles for Financial Market Infrastructures (PFMI). It has a sound, coherent and transparent legal basis. As an integral part of the Hong Kong Exchanges and Clearing Limited (HKEX Group), the HKCC has a comprehensive and adequate risk management framework to address financial, business, and operational risks. Participant assets as well as HKCC's collaterals are safely kept in several banks and regulated central securities depositories. The credit and liquidity risks are minimized by having a robust risk management framework, including rigorous stress testing methodology and access to qualifying liquid resources. Furthermore, the HKCC has clear rules and procedures to handle and manage a participant's default procedures. Moreover, the HKCC has established risk management framework to handle operational risk, including cyber risk, and business continuity management that addresses events posing significant risk of operational disruption.